Restructuring options in commercial bankruptcy: A legal analysis under the Saudi law - Almalki, Adnan Ayza (Edelweiss Applied Science and Technology, 2025)
This research examines how the bankruptcy law has operated in Saudi Arabia since its implementation in 2018. This law was enacted to help develop the economy and support small and medium-sized companies in line with Saudi Vision 2030. The research used a legal analytical approach to legal texts and examined some bankruptcy cases that were subject to the new bankruptcy law. The study found that the new law has improved business conditions by providing options beyond simply closing. Businesses can now reorganize and survive during difficult times. However, businesses may face some difficulties and time-consuming procedures to legally resolve bankruptcy. The research indicates that more businesses are using settlement options to avoid bankruptcy, indicating growing confidence in the law. The research highlights the need to better spread legal awareness about the bankruptcy law, expedite procedures, and educate small business owners about the law. These changes will make the Saudi economy stronger and more attractive for investment, helping to achieve the goals of Vision 2030.